Walking as Embodied Territorial Acknowledgment: Thinking about Place-Based Relationships from the Side of the Road - Wilson, Ken (Performance Matters, 2021)
This paper is a meditation on the possibilities of walking performance as an embodied territorial acknowledgement. It discusses the problems of verbal territorial or treaty acknowledgements, and asks whether embodied territorial acknowledgements might overcome those problems. It asks whether settlers walking on the land can begin to enter into a kinship relationship with it, or whether they are locked into scopophilic and extractive ways of experiencing the land and are therefore incapable of seeing themselves and the land as sharing kinship ties. The paper’s theoretical discussions are grounded in accounts of walking performances the author has made in and around Regina, Saskatchewan, a city in Treaty 4 territory.